Biofilm formation to inhibition: role of zinc oxide-based nanoparticles - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Badiger, Manohar V.; Patel, Pratikshkumar R.; Thorat-Gadgil, Bhagyashi S.; Pandit, Abhay; Bohara, Raghvendra A. (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Zinc oxide nanoparticles have received much attention worldwide as they possess unique properties like varied morphology, large surface area to volume ratio, potent antibacterial activity, and biocompatibility. Biofilm contains homogenous or heterogeneous microorganisms that remain enclosed in a matrix of an extracellular polymeric substance on biotic or abiotic surfaces. Bacterial biofilm formed on medical devices such as central venous catheters, urinary catheters, prosthetic joints, cardiovascular implantable devices, dental implants, contact lenses, intrauterine contraceptive devices and breast implants cause persistent infections. Such biofilm-associated infections in medical implants cause serious problems for public health and affect the function of medical implants. So, there is an urgent need for the use of an antimicrobial agent that will inhibit biofilm, including such antibiotic-resistant bacterial strains as bacteria, to develop multiple drug-resistances resulting in failure of the antibiotic's action. The antimicrobial agent used should be ideal in terms of biocompatibility, antimicrobial activity, stability at different environmental conditions, with less sensitivity to the development of resistance towards micro-organisms, safe for in vivo and in vitro use, and remain non-hazardous to the environment, etc. The first objective of the review discusses the insights into the formation of biofilm on a medical device with the current strategies to inhibit. The second purpose is to review the recent progress in ZnO- based nanostructure including composites for antibacterial and anti-biofilm activities. This will offer a new opportunity for the application of Zinc oxide-based material in the prevention of biofilm on the medical devices.
Keywords: antibacterial activity; Antibiofilm agent; Biocompatibility; Biofilm; Nanocomposites; ZnO nanoparticles

Electrospun poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/polyethylene oxide (PEO) microfibers reinforced with ZnO nanocrystals for antibacterial and antibiofilm wound dressing applications - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Patel, Pratikshkumar R.; Dhanavade, Maruti J.; Badiger, V. Manohar; Marathe, Yogesh N.; Bohara, Raghvendra A. (New Journal of Chemistry, 2020)
Biocompatible and biodegradable polymers are extensively used in designing wound dressing materials. The present investigation deals with the preparation of a unique blend of zinc oxide (ZnO) nanoparticles incorporated in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/polyethylene oxide (PEO) microfibersviaan electrospinning technique for antibacterial, antibiofilm and wound dressing applications. This composite was prepared by incorporating previously synthesized ZnO NPs with better antibacterial and antibiofilm activity in PHBV-PEO (4 : 1) polymers in chloroform solution. Scanning electron microscopy (SEM) and Fourier transform infrared (FT-IR) spectroscopy confirmed that ZnO NPs were incorporated in the PHBV-PEO microfibers. The synthesized microfibers exhibited enhanced mechanical properties after the incorporation of ZnO NPs. The results of antibacterial and antibiofilm activity of the prepared microfibers revealed that the incorporated ZnO NPs in different concentrations (1%, 3%, and 5%) showed different degrees of antibacterial activity against pathogenic Gram-positiveStaphylococcus aureus(NCIM 2654) and Gram-negativePseudomonas aeruginosa(NCIM 5032), which are the main bacteria found in wound infections. The PHBV-PEO-ZnO microfibers exhibited excellent hemocompatibility with improved swelling behavior after the incorporation of ZnO NPs.In vitrocytotoxicity assays revealed the non-toxic nature of the prepared PHBV-PEO-ZnO microfibers. The current work confirms that utilizing a unique blend of the biodegradable, biocompatible, thermoplastic and hydrophobic natural polymer PHBV with hydrophobic, biodegradable, non-toxic and synthetic polymer PEO with ZnO NPs holds great potential for use as an antibacterial and antibiofilm material for wound dressing applications.